Neonatal resuscitation skills acquisition among healthcare providers after Helping Babies Breathe simulation training using improved tools across two regions in Tanzania - Florence Salvatory Kalabamu; Vickfarajaeli Daudi; Robert Moshiro; Benjamin Kamala; Paschal Mdoe; Dunstan Bishanga; Hege Ersdal; Rose Mpembeni (Advances in Simulation)
Abstract Introduction Neonatal mortality is high in middle- and low-income countries, including Tanzania. Most of these deaths are preventable and linked to suboptimal quality of care. In this study, we assessed neonatal resuscitation skills acquisition after a 1-day Helping Babies Breathe (HBB) simulation training using improved tools and associated factors among healthcare providers in 12 facilities in Tanzania. Methods A cross-sectional study was conducted among healthcare providers working in the labor wards in selected health facilities. The training was conducted in situ using the HBB second edition curriculum with improved simulation tools (Neonatalie Live simulator, NeoBeat heart rate meter, and Upright resuscitator). After training, skills acquisition was evaluated using Objectively Structured Clinical Evaluation. Participants who scored an average of 75% or above were considered passing. Descriptive statistics were used to determine the proportion of staff who passed the evaluation by different demographic categories. One-way analysis of variance was used to compare mean scores among demographic categories. Factors associated with neonatal resuscitation skills acquisition were analyzed using modified Poisson regression. Results A total of 481 participants were enrolled in the study. Among these, 420 (87.3%) passed the skills evaluation on the first attempt. The overall mean skills score was 92.4%. In bivariable analysis, health facility level, region, age, and experience working in the labor ward were associated with passing skills evaluation on the first attempt. However, after controlling other variables in a multivariable model, none of the factors showed a statistically significant association. Conclusion In-situ, HBB simulation training using improved training tools effectively imparts neonatal resuscitation skills among healthcare providers. Participants learned skills similarly regardless of their different demographic characteristics, including level of education and working experience. Due to its potential to impart skills, frequent simulation training using improved tools may be considered for scaling up in other health facilities.